Peran Aktif Mahasiswa KKN dalam Pengembangan Pendidikan di SDN 6 Telangkah - Ainni Ainni; Reza Nadia; Indah Setiawati; Husniah Husniah; Rabiah Al-Adawiyah; Raihan Nadhir; Muhammad Jumadin Noor; Mila Mila (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The Community Service Program (KKN) at SDN 6 Telangkah, Desa Hampalit, was chosen as a topic for community engagement due to the need for improving the quality of education. Given the challenges of access and quality in education, KKN serves as an important means to empower the community and integrate theory with practice. The method used is participatory, involving teachers, students, and staff at every stage of the activities, from problem identification to evaluation. Activities included the